Socio-Demographic and Psychological Factors Influencing the Happiness of Gyeongsangbuk-do Residents. - Sung Jung Hong; See Jo Kim; Nam Hyun Cha (Research in Community & Public Health Nursing (RCPHN), 2025)
Purpose: This study examined the effects of sociodemographic factors, health behavior, and psychological-emotional characteristics on stress, depression, and happiness among residents of Gyeongsangbuk-do and explored the relationships among these variables. Methods: A cross-sectional analysis was conducted using data from the 2022 Korean Community Health Survey. The sample included 21,490 residents of Gyeongsangbuk-do. Multiple linear regression and Pearson correlation analyses were performed to identify predictors of psychological well-being. Results: Participants showed high prevalence of health risk behaviors, including alcohol consumption (76.4%) and smoking (15.7%), while a majority engaged in regular physical exercise (79.3%). Despite this, the proportion reporting good or very good subjective health was lower than the national average (34.0% vs. 53.1%). Stress was positively correlated with depression (r=.24, p<.001) and negatively correlated with happiness (r=-.25, p<.001). Multiple regression analysis revealed that happiness was significantly associated with subjective health status (β=.07 to .27), stress (β=-.19), depression (β=-.17), suicidal thoughts (β=-.11), educational attainment (β=.03 to .10), smoking (β=-.08), physical exercise (β=.04), and income level (β=-.03 to .04). The final model explained 25.6% of the variance in happiness (adjusted R²=.256, F=337.76, p<.001). Conclusion: Happiness among Gyeongsangbuk-do residents was influenced by a combination of sociodemographic, health behavioral, and psychological-emotional factors. These findings provide foundational evidence for developing regionally tailred strategies to improve community mental well-being.